2002
DOI: 10.1128/cdli.9.2.352-357.2002
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Dietary Lipids as Modulators of Immune Functions in Cells Infected with Listeria monocytogenes

Abstract: Nutritional status may have significant importance for the immune system, and particularly, unsaturated fatty acids may serve as modulators of immune functions. Clinical and epidemiological studies have demonstrated that fatty acids are involved in the reduction of the inflammatory processes that occur in diseases characterized by an overactivation of the immune system. At the same time, an increase in susceptibility to infection has also been reported. The importance of immune system modulation by dietary lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…(Data are taken from Kew et al 2004. ) Listeria monocytogenes to adhere to or invade the cells in vitro (Puertollano et al 2002). Also, the same group investigated the effects of diets containing hydrogenated coconut oil, sunflower oil and olive oil on phagocytic activity in Balb/c mice and demonstrated that the olive oil diet enhanced phagocytic activity and production of IL-1 relative to the other groups (De Pablo et al 1998b).…”
Section: Dietary Fatty Acids and Host Defencementioning
confidence: 99%
“…(Data are taken from Kew et al 2004. ) Listeria monocytogenes to adhere to or invade the cells in vitro (Puertollano et al 2002). Also, the same group investigated the effects of diets containing hydrogenated coconut oil, sunflower oil and olive oil on phagocytic activity in Balb/c mice and demonstrated that the olive oil diet enhanced phagocytic activity and production of IL-1 relative to the other groups (De Pablo et al 1998b).…”
Section: Dietary Fatty Acids and Host Defencementioning
confidence: 99%
“…Immunological changes that are associated with the metabolic and physical stresses of parturition increase in the weeks before calving and peak at parturition (Mallard et al, 1998;Mallard, 1999); -E-mail: valerio.bronzo@unimi.it however, data on the immune status of dairy goats in the peripartum period are limited (Azab et al, 1999;Agazzi et al, 2004). Previous research in animal models has identified several nutritional approaches that may modulate the production of key factors involved in the activation and regulation of innate and adaptive immunity (Calder, 1997;Puertollano et al, 2002;Lessard et al, 2004). Gershwin et al (1985) and Johnston (1988) observed that both cell-mediated immunity and humoural immunity are influenced by the amount and types of fat in the diet, while Calder and Grimble (2002) presented evidence that fatty acids (FAs) can act as second messengers or regulators of signal transduction molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, several studies have reported that an excess intake of n-3 polyunsaturated fatty acids may cause undesirable effects in both humans and animals, because they are able to reduce host immune resistance against infectious microorganisms (1,11). Thus, numerous investigations have indicated that diets containing n-3 polyunsaturated fatty acids enhance susceptibility to infection by Listeria monocytogenes (8,13,23), Salmonella enterica serovar Typhimurium (7), Mycobacterium tuberculosis (21), or Pseudomonas aeruginosa (22), whereas other recent observations have reported that these diets increase immune resistance against Klebsiella pneumoniae (2,3,27), although these effects could not be demonstrated in infection with Streptococcus pneumoniae (27). Therefore, it is possible that the consequences derived from the reduction of immune resistance by n-3 polyunsaturated fatty acids may also depend on the type of microorganisms and their pathogenic mechanisms.…”
mentioning
confidence: 99%